Perancangan dan Implementasi Broadband Wireless Acces Berbasis 802.11ac pada Jaringan Provider Zettalink - Guswita, Nadia; Yolanda, Amelia; Khair, Ummul; Lisyadi Oktapianus, Yoppi (Jurusan Teknik Elektro Fakultas Teknik Universitas Bangka Belitung, 2024)
Broadband Wireless Access (BWA) is a type of wireless local area network known for its ability to support a large number of users, wide coverage, and high speed, in accordance with the IEEE 802.16 standards. As the demand for stable and fast internet access continues to grow, some areas, including Lembah Gumanti District, face challenges in developing telecommunications infrastructure. This research aims to establish a BWA network to enhance the quality of connectivity in the district. Most current WLAN networks operate on the 2.4GHz frequency using the IEEE 802.11g and 802.11n standards, which often experience interference issues. In this study, the IEEE 802.11ac standard, which operates exclusively on the 5GHz frequency, is employed to avoid interference associated with the 2.4GHz range and support channel widths of up to 80MHz, thereby improving network efficiency. Zettalink is strategically positioned to implement BWA technology based on 802.11ac in rural areas like Lembah Gumanti. Unlike the expensive and subscription-based WiMAX technology, 802.11ac offers more affordable access solution for rural regions. The network is designed using a Point-to-multipointmethod with sectoral and omnidirectional Antennas, tailored to the hilly and humid geographical conditions of Lembah Gumanti. The primary focus of this research includes network design with the UISP Design Center, analysis of the application of sectoral Antennas using Ubiquiti LiteBeam M5, and calculations of device receiving power. The main challenges in this implementation include the risk of interference due to humid weather and high rainfall, as well as the high costs associated with the procurement of equipment